The t(8;17)(p11;q23) in the 8p11 myeloproliferative syndrome fuses MYO18A to FGFR1 - Walz, Christoph; Chase, A.; Schoch, C.; Weißer, Andreas; Schlegel, F.; Hochhaus, Andreas; Fuchs, R.; Schmitt-Gräff, A.; Hehlmann, Rüdiger; Cross, N. C. P.; Reiter, Andreas (Leukemia, 2005)
The 8p11 myeloproliferative syndrome (EMS) also known as stem cell leukemia-lymphoma syndrome (SCLL) is associated with translocations that disrupt FGFR1. The resultant fusion proteins are constitutively active tyrosine kinases, and different FGFR1 fusions are associated with subtly different disease phenotypes. We report here a patient with a t(8;17)(p11;q23) and an unusual myelodysplastic/myeloproliferative disease (MDS/MPD) characterized by thrombocytopenia due to markedly reduced size and numbers of megakaryocytes, with elevated numbers of monocytes, eosinophils and basophils. A novel mRNA fusion between exon 32 of the myosin XVIIIA gene (MYO18A) at chromosome band 17q11 and exon 9 of FGFR1 was identified. Partial characterization of the genomic breakpoints in combination of bubble-PCR with fluoresence in situ hybridization revealed that the t(8;17) arose from a three-way translocation with breaks at 8p11, 17q11 and 17q23. MYO18A-FGFR1 is structurally similar to other fusion tyrosine kinases and is likely to be the causative transforming lesion in this unusual MDS/MPD.
Gesehen am 11.05.2022